Analisis Kinerja Frame Relay Pada Cloud Router dan PC Berbantuan Cisco Packet Tracer Student - Fadel Montoya; Enjel Rosiana; Ilham Firdaus; Didik Aribowo (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Data networks are the lifeblood of modern life, connecting people and information at high speeds. Frame Relay technology plays an important role in delivering efficient and reliable data connectivity, like a water pipe that flows information seamlessly. Specifically designed for Wide Area Network (WAN), Frame Relay works at layer 2, optimizing data transmission between remote locations. This research uses experimental research. Experimental research is a manipulative process that needs to be carried out by applying certain treatments/treatments to research subjects and observing/measuring the effects. This research was conducted by looking at the results of the ping test on Router 1, Router 2 and Router 3 in sending messages over the network in 1 cloud The "ping" command is used to test the network connection by sending packets to the specified IP address. The results of the "ping" command show that the network connection to IP address 192.168.5.100 can be guaranteed successfully, with an average response time of about 16 ms. The frame relay circuit on the cloud router uses frame relay technology to send data between connected devices. The cloud router becomes the center of the frame relay network and manages the data traffic between the devices. IP network configuration can be done automatically through DHCP Ping also shows that the network is reliable with a minimum response time of 13 ms, a maximum of 19 ms, and an average of 16 ms.